2005
DOI: 10.7498/aps.54.5618
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit ab initio study of the S2(B3Σ-u→X3Σ-g(ν′≥18,0)) diffuse bands

Abstract: The diffuse bands B3Σ-u→X3Σ-g(ν′≥18,0) of diatomic molecule S2 observed in the experiment are investigated. The electronic potential curves,including the spin-orbit coupling (SOC) effect of B3Σ-u and repulsive 15Πu, 23Σ+u states are calculated. For the diffuse bands beginning at (18,0), a point of view different from others' results is presented in this work. Our results indicate that the SOC induced predissociation between B3Σ-u and 15Πu, 23Σ+u plays the key role in the diffusion of spectra. Comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…The 1 5 Π u0 state, through its outer-limb crossing with the B state and a large spin-orbit interaction matrix element, is the primary route for the predissociation of the B 3 Σ − u0 (v ≥ 18) levels. This conclusion is consistent with the results of Yan et al, 15,16 where an ab initio value of ∼160 cm −1 was found for the spin-orbit coupling at the crossing point, 9% less than the present value. The 1 1 Σ + u state, through a strong isoconfigurational spinorbit interaction of 409(15) cm −1 with B 3 Σ − u0 , 25 depresses its levels, thus making a significant second-order spin-orbit contribution to the effective spin-spin constant for the B state.…”
Section: Basic Model: 0 + U Statessupporting
confidence: 94%
See 3 more Smart Citations
“…The 1 5 Π u0 state, through its outer-limb crossing with the B state and a large spin-orbit interaction matrix element, is the primary route for the predissociation of the B 3 Σ − u0 (v ≥ 18) levels. This conclusion is consistent with the results of Yan et al, 15,16 where an ab initio value of ∼160 cm −1 was found for the spin-orbit coupling at the crossing point, 9% less than the present value. The 1 1 Σ + u state, through a strong isoconfigurational spinorbit interaction of 409(15) cm −1 with B 3 Σ − u0 , 25 depresses its levels, thus making a significant second-order spin-orbit contribution to the effective spin-spin constant for the B state.…”
Section: Basic Model: 0 + U Statessupporting
confidence: 94%
“…where V ∞ is the energy of the relevant dissociation limit, R x is the crossing point with the bound-state PEC, V x is the excess energy above dissociation at the crossing point, and M x is the magnitude of the slope of the exponential curve at the crossing point. The fitting process yielded R x = 2.816(1) Å and M x = 8800(100) cm −1 /Å for the 1 5 Π u0 PEC, which are in fairly good agreement with ab initio values deduced from the work of Yan et al, 15,16 R x = 2.829 Å and M x ≈ 8000 cm −1 /Å, respectively. The fitted interaction matrix elements for Ω = 0 contributing to the B 3 Σ − u0 -state predissociation are listed in the third column of Table I.…”
Section: Basic Model: 0 + U Statessupporting
confidence: 84%
See 2 more Smart Citations
“…Wheeler et al, 25 as part of their combined experimental and modeling study, calculated ab initio curves for the B and 1 1 Π u states. Yan et al 31 and Xing et al 32 present ab initio potential curves and evaluate spin-orbit coupling between the B state and the ungerade states that may contribute to its predissociation.…”
Section: Introductionmentioning
confidence: 99%